2021
DOI: 10.1136/bmjopen-2020-043060
|View full text |Cite
|
Sign up to set email alerts
|

Key dimensions of post-traumatic stress disorder and endothelial dysfunction: a protocol for a mechanism-focused cohort study

Abstract: IntroductionBoth trauma exposure and post-traumatic stress disorder (PTSD) are associated with increased risk of cardiovascular disease (CVD), the leading cause of death in the USA. Endothelial dysfunction, a modifiable, early marker of CVD risk, may represent a physiological mechanism underlying this association. This mechanism-focused cohort study aims to investigate the relationship between PTSD (both in terms of diagnosis and underlying symptom dimensions) and endothelial dysfunction in a diverse, communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
(105 reference statements)
0
2
0
1
Order By: Relevance
“…Недостатня вазодилатація в умовах підвищеного серцево-судинного навантаження призводить до збільшення жорсткості судинної стінки, запальної реакції та активації протромботичних процесів [79]. Два дослідження, які оцінювали зв'язок ПТСР з ЕД, виявили, що в пацієнтів з ПТСР спостерігалося клінічно значуще зниження потокозалежної вазодилататорної відповіді плечової артерії, за даними тесту з реактивною гіперемією [16,30]. ЕД разом із гіперкоагуляційним станом може сприяти гострим атеротромботичним серцево-судинним подіям [5].…”
Section: механізми взаємозв'язку птср -ссз [49]unclassified
“…Недостатня вазодилатація в умовах підвищеного серцево-судинного навантаження призводить до збільшення жорсткості судинної стінки, запальної реакції та активації протромботичних процесів [79]. Два дослідження, які оцінювали зв'язок ПТСР з ЕД, виявили, що в пацієнтів з ПТСР спостерігалося клінічно значуще зниження потокозалежної вазодилататорної відповіді плечової артерії, за даними тесту з реактивною гіперемією [16,30]. ЕД разом із гіперкоагуляційним станом може сприяти гострим атеротромботичним серцево-судинним подіям [5].…”
Section: механізми взаємозв'язку птср -ссз [49]unclassified
“…Novel studies reported premature endothelial senescence in veterans and non-veterans with PTSD, indicating that BBB disruption likely plays a pivotal role in this disorder (Boscarino, 2008;Grenon et al, 2016;Thurston et al, 2018). Others have found that war veterans with PTSD, like older individuals, present with defective mitochondria, telomeres, furin/plasmin, and BDNF, connecting cerebral EC senescence with dysfunctional subcellular structures (Levin et al, 1997;Doughan et al, 2008;Gray and Ellis, 2008;Fleegal-DeMotta et al, 2009;Khoury et al, 2012;Grenon et al, 2016;Aksu et al, 2018;Connolly et al, 2018; Stein et al, 2018;Miranda et al, 2019;Seligowski et al, 2021;Cleveland et al, 2021).…”
Section: Furin Cleaving Site and Ptsdmentioning
confidence: 99%
“…Thus, disturbed regulation of CBF can play an important role in the high risk of both cardiovascular and mental disorders following severe stress [ 7 ]. Accordingly, special attention should be paid to endothelial dysfunction [ 13 , 14 , 15 ] as a factor affecting CBF after severe stress.…”
Section: Introductionmentioning
confidence: 99%